The Uridylyl Transferase TUT7‐Mediated Accumulation of Exosomal miR‐1246 Reprograms TAMs to Support CRC Progression - Yifei Feng; Chi Jin; Tuo Wang; Zhihao Chen; Dongjian Ji; Yue Zhang; Chuan Zhang; Dongsheng Zhang; Wen Peng; Yueming Sun (Advanced Science, 2024)
Abstract Tumor‐associated macrophages (TAMs) play a crucial role in promoting tumor growth and dissemination, motivating a search for key targets to interfere with the activation of TAMs or reprogram TAMs into the tumor‐suppressive type. To gain insight into the mechanisms of macrophage polarization, a designed co‐culture system is established, allowing for the education of macrophages in a manner that closely mimics the intricacies of TAMs in the tumor immune microenvironment (TIME). Through database mining, exosomal miR‐1246 is identified and is then validated. Exosomal miR‐1246‐driven polarization of TAMs disrupts the infiltration and function of CD8+ T cells. Mechanically, the amassment of exosomal miR‐1246 stems from TUT7‐mediated degradation of small noncoding RNA, a process stabilized by SNRPB, but not the precursor of miR‐1246. Moreover, an Exo‐motif is present in the exosomal miR‐1246 sequence, enabling it to bind with the exosomal sorting protein hnRNPA2B1. RNA‐seq analysis reveals that exogenous miR‐1246 modulates the polarization of TAMs at a post‐transcriptional level, emphasizing the pivotal role of the NLRP3 in macrophage polarization. In conclusion, the findings underscore the importance of exosomal miR‐1246 as a trigger of macrophage reprogramming and uncover a novel mechanism for its enhanced presence in the TIME.